Profiling of immunoglobulins in resting and mechanically stimulated saliva. (March 2014) - MacDonald, Michael; Ghani, Nur Aziemah Ab; Wan, Yunxia; Cooper-White, Justin; Dimeski, Goce; Punyadeera, Chamindie
Background: Dysregulation of salivary immunoglobulins has been implicated in illnesses ranging from periodontal disease to HIV aids and malignant cancers. Despite these advances there is a lack of agreement among studies with regard to the salivary immunoglobulin levels in healthy controls.Methodology: Resting and mechanically stimulated saliva samples and matching serum samples were collected from healthy individuals (n = 33; 40–55 years of age; gender: 23 female, 10 male). A matrix-matched AlphaLISA ® assay was developed to determine the concentrations of IgG1 and IgG4 in serum and saliva samples.Conclusion: Clear relationships were observed in the flow rate and concentration of each immunoglobulin in the two types of saliva. This study affirms the need to establish and standardize collection methods before salivary IgGs are used for diagnostic purposes.